2004
DOI: 10.1099/jmm.0.05415-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and molecular epidemiology of Brachyspira pilosicoli in humans on the island of Bali, Indonesia

Abstract: The purpose of this study was to investigate the prevalence and epidemiology of the anaerobic intestinal spirochaete Brachyspira pilosicoli amongst Indonesians living in rural and urban settings on the island of Bali. Faecal samples (n ¼ 992) were collected on two occasions, 4 months apart, from people living in four traditional farming villages, one peri-urban location and one urban area. Samples were cultured anaerobically on selective agar and intestinal spirochaete isolates were confirmed to be B. pilosico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 36 publications
3
45
0
4
Order By: Relevance
“…Again, colonization was restricted to the Aboriginal and migrant groups, but with the apparent prevalence of faecal shedding increased to levels more consistent with that previously described in Aboriginal children in a remote rural community in WA (33 %) [12], and to those of villagers in Papua New Guinea (23 %) [9], India (25 %) [11], and Bali, Indonesia (12 %) [10]. Apart from the presence of B. aalborgi, which was significantly associated with the presence of B. pilosicoli in both population groups, and in the previous study from India [11], the new analysis did not strengthen the identification of significant risk factors.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Again, colonization was restricted to the Aboriginal and migrant groups, but with the apparent prevalence of faecal shedding increased to levels more consistent with that previously described in Aboriginal children in a remote rural community in WA (33 %) [12], and to those of villagers in Papua New Guinea (23 %) [9], India (25 %) [11], and Bali, Indonesia (12 %) [10]. Apart from the presence of B. aalborgi, which was significantly associated with the presence of B. pilosicoli in both population groups, and in the previous study from India [11], the new analysis did not strengthen the identification of significant risk factors.…”
Section: Discussionsupporting
confidence: 77%
“…Apart from the presence of B. aalborgi, which was significantly associated with the presence of B. pilosicoli in both population groups, and in the previous study from India [11], the new analysis did not strengthen the identification of significant risk factors. It was unfortunate that data were not available on water supply or water quality, as in previous studies in both India and Bali the use of untreated well water was associated with increased B. pilosicoli carriage [10,11]. Differences in water quality might have helped explain the different prevalence observed amongst population groups in this study.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Infections with B. pilosicoli are common amongst intensively farmed pigs and chickens, where they cause diarrhoea and reduced production (Hampson & Duhamel, 2006;Hampson & Swayne, 2008). Colonization also is common in people living in crowded and unhygienic conditions in developing countries (Trott et al, 1997;Margawani et al, 2004;Nelson et al, 2009), as well as in homosexual males and HIV-positive individuals in developed countries (Law et al, 1994;Trivett-Moore et al, 1998). In some studies, colonization in humans has been found to be significantly associated with chronic diarrhoea, failure to thrive and being underweight (Brooke et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Colonization with B. pilosicoli is common (10-50 % prevalence) in people living in developing countries, including Gulf Arabs in Oman (Barrett, 1990), villagers in Papua New Guinea (PNG) (Trott et al, 1997a), villagers and peri-urban residents in Bali, Indonesia (Margawani et al, 2004) and villagers in tea plantations in India (Munshi et al, 2004). In developed countries, including the UK and Australia, the spirochaete is rarely isolated from individuals in the general population (Tompkins et al, 1986;Brooke et al, 2006), although prevalence rates reach the high levels seen in developing countries in Australian Aborigines living in remote communities (Lee & Hampson, 1992;Brooke et al, 2001Brooke et al, , 2006, homosexual males and HIV patients (Käsbohrer et al, 1990;Trivett-Moore et al, 1998) and immigrants on arrival from developing countries (Brooke et al, 2001(Brooke et al, , 2006).…”
Section: Introductionmentioning
confidence: 99%